2007
DOI: 10.1152/japplphysiol.01155.2006
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular and capillary perfusion following glycocalyx degradation

Abstract: Systemic parameters and microvascular and capillary hemodynamics were studied in the hamster window chamber model before and after hyaluronan degradation by intravenous injection of Streptomyces hyaluronidase (100 units, 40-50 U/ml plasma). Glycocalyx permeation was estimated using fluorescent markers of different molecular size (40, 70, and 2,000 kDa), and electrical charge. Systemic parameters (blood pressure, heart rate, blood gases) and microhemodynamics (vascular tone, velocity, and blood flow) remained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
105
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 33 publications
(56 reference statements)
9
105
3
3
Order By: Relevance
“…39,41,45 In addition to the tight junctions in between endothelial cells, the SGL plays an important role in maintaining the barrier function of endothelium due to its matrix-like structure as well as the charge. 1,9,11,18,39,44 Yuan et al 46 found that the permeability of intact rat pial microvessels to positively charged ribonuclease was four times as large as that to negatively charged a-lactalbumin, though they have almost the same size. Combining these measured permeability data with a mathematical model, they predicted that the charge density is~30 mEq/L in the structural components of the BBB, i.e., the SGL and the basement membrane.…”
Section: Introductionmentioning
confidence: 99%
“…39,41,45 In addition to the tight junctions in between endothelial cells, the SGL plays an important role in maintaining the barrier function of endothelium due to its matrix-like structure as well as the charge. 1,9,11,18,39,44 Yuan et al 46 found that the permeability of intact rat pial microvessels to positively charged ribonuclease was four times as large as that to negatively charged a-lactalbumin, though they have almost the same size. Combining these measured permeability data with a mathematical model, they predicted that the charge density is~30 mEq/L in the structural components of the BBB, i.e., the SGL and the basement membrane.…”
Section: Introductionmentioning
confidence: 99%
“…As shown therein, no significant change in arteriolar or venular hematocrit occurred with fMLP, as assessed by direct spectrophotometric methods. In contrast, H CAP was found to increase in response to degradation of the glycocalyx twofold with direct infusion of heparinase with micropipettes (13) and systemic infusion of hyaluronidase (7). Systemic infusion of oxidized LDL increased it twofold (10), and sustained epifluorescence illumination increased it by 68% (59), presumably due to generation of reactive oxygen species in both studies.…”
Section: Discussionmentioning
confidence: 97%
“…Experimental manipulations of the structure of the glycocalyx by perfusion of the microvasculature with heparinase have revealed decreases in intravascular resistance to flow (50). Increases in capillary hematocrit (H CAP ) have been attributed to removal of the glycocalyx in response to perfusion with heparinase (13) and hyaluronidase (7) and the presence of reactive oxygen species derived from oxidized low-density lipoprotein (LDL) (10). Thus the structure of the glycocalyx is a prime determinant of numerous physiological and hemodynamic processes, and maintenance of its stability may preclude the onset of many pathological disturbances (5).…”
mentioning
confidence: 99%
“…Loss of endothelial glycocalyx integrity after ischemia and reperfusion has been observed in experimental models (8,24,27) and in patients undergoing aortic surgery (28). Degradation of the endothelial glycocalyx by infusion of hyaluronidase causes capillary perfusion defects in rodents (7). Taken together, ischemic injury to endothelial cells and glycocalyx of peritubular capillaries may play a major role in the pathophysiology of acute kidney injury by reducing tissue perfusion and propagating inflammation in the reperfused kidney.…”
mentioning
confidence: 99%